ANALISIS KELAYAKAN POLA USAHATANI SAYURAN DI DESA TUGU MULYO KECAMATAN BELITANG MADANG RAYA KABUPATEN OKU TIMUR (JASEP, 2018)
This study aims to analyze the feasibility of vegetable farming pattern in Tugu Mulyo Village Belitang Madang Raya District, OKU Timur Regency. The sampling method used in this research is the unbalanced random sampling method (disproportionated stratified random sampling). The results obtained in this study are (1) Revenue obtained in pattern I with net income of Rp. 10,748,317 of all farmers' average farming income, pattern II with net income of Rp. 20,736,017 of all farmers' farming and pattern III earnings with net income of Rp. 8,663,850 of all farmers' average farming earnings. (2) the most feasible farming pattern for farming system II is big chilli plant with cauliflower because R/C biggest, with value R/C 2.0 then farming pattern is most feasible for farming in District Belitang Madang Raya Desa Tugu Mulyo.